Effects of replacing Carbon Black with Wood Fibers in wood-rubber composites - Raia, Renan Zunta; Iwakiri, Setsuo; Trianoski, Rosilani; de Andrade, Alan Sulato; Kowalski, Edemir Luiz; Job, Aldo Eloizo [UNESP]; de Paiva, Fábio Friol Guedes (FapUNIFESP (SciELO), 2023)
The objective of this research was to develop a more sustainable composite and still keep its characteristics. Fibers treated with NaOH at 5% w/w for 2 hours were incorporated into natural rubber in different proportions (0 phr, 24 phr, 36 phr, 48 phr and 60 phr). The mechanical properties of the composites suffered changes, increasing the hardness, young’s modulus and decreasing its tensile strength. All the physical properties were not statistically different. The coloration became less dark in the WF60/CB0 treatment, and the electrical properties presented better resistivity with the increase in the concentration of fibers in the composite. This presents a possibility of using WF for the production of wood-rubber composites for the production of rubber artifacts which do not require high rolling resistance. Based on the results from this research, we recommended the WF24/CB36 mix to produce antistatic floors.
Keywords: carbon black; composite; composite properties; natural rubber; wood fibers